2017
DOI: 10.1007/s10068-017-0277-x
|View full text |Cite
|
Sign up to set email alerts
|

Whole grain cereal attenuates obesity-induced muscle atrophy by activating the PI3K/Akt pathway in obese C57BL/6N mice

Abstract: Whole grain comprises starchy endosperm, germ, and bran tissues, which contain fibers, minerals, vitamins, and several phytochemicals. Whole grain cereal (WGC)-based food products supply beneficial nutrients (essential for health care) and macronutrients (essential for body maintenance and support). The present study investigated the inhibitory effect of WGC on obesity-induced muscle atrophy in obese C57BL/6N mice. WGC attenuated the body weight gain, fat pad mass, adipocyte size, food efficiency ratio, serum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…Values are presented as median (interquartile range) 1) Analyzed by the Kruskal Wallis test for WD-CRD-MRD groups 2) Analyzed by the Mann-Whitney U test for change between WD-MRD 3) Analyzed by the Mann-Whitney U test for change between WD-CRD 4) Analyzed by the Mann-Whitney U test for change between MRD-CRD Abbreviations: WD Wellnessup diet, MRD maintaining regular diet, CRD calorie-restricted diet, MET metabolic equivalent Similar to our research, a study Yurrita et al (2017) [26] have reported that significant decreases in body weight, BMI and body fat percentage and greater loss of musculature were observed in the detox diet group(based on juices for 3 days, followed by a hypocaloric diet for 4 days)than in Mediterranean diet group (a hypocaloric Mediterranean diet for 7 days). A study by Lee et al (2017) [44] indicated that whole grain cereal effectively attenuates obesity-related skeletal muscle atrophy as well as overall obesity in obese mice. Because of supplementation of whole grain cereal, which contains of beneficial minerals, vitamins, and other phytochemicals, it suggests that may have helped not only suppress muscle atrophy but also weight loss by activating the phosphatidylinositol 3-kinase and protein kinase B pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Values are presented as median (interquartile range) 1) Analyzed by the Kruskal Wallis test for WD-CRD-MRD groups 2) Analyzed by the Mann-Whitney U test for change between WD-MRD 3) Analyzed by the Mann-Whitney U test for change between WD-CRD 4) Analyzed by the Mann-Whitney U test for change between MRD-CRD Abbreviations: WD Wellnessup diet, MRD maintaining regular diet, CRD calorie-restricted diet, MET metabolic equivalent Similar to our research, a study Yurrita et al (2017) [26] have reported that significant decreases in body weight, BMI and body fat percentage and greater loss of musculature were observed in the detox diet group(based on juices for 3 days, followed by a hypocaloric diet for 4 days)than in Mediterranean diet group (a hypocaloric Mediterranean diet for 7 days). A study by Lee et al (2017) [44] indicated that whole grain cereal effectively attenuates obesity-related skeletal muscle atrophy as well as overall obesity in obese mice. Because of supplementation of whole grain cereal, which contains of beneficial minerals, vitamins, and other phytochemicals, it suggests that may have helped not only suppress muscle atrophy but also weight loss by activating the phosphatidylinositol 3-kinase and protein kinase B pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our research, a study Yurrita et al (2017) [26] have reported that signi cant decreases in body weight, BMI and body fat percentage and greater loss of musculature were observed in the detox diet group(based on juices for 3 days, followed by a hypocaloric diet for 4 days)than in Mediterranean diet group (a hypocaloric Mediterranean diet for 7 days). A study by Lee et al (2017) [44] indicated that whole grain cereal effectively attenuates obesity-related skeletal muscle atrophy as well as overall obesity in obese mice. Because of supplementation of whole grain cereal, which contains of bene cial minerals, vitamins, and other phytochemicals, it suggests that may have helped not only suppress muscle atrophy but also weight loss by activating the phosphatidylinositol 3-kinase and protein kinase B pathway.…”
Section: Discussionmentioning
confidence: 99%
“…For epididymal adipose tissue, RNA was isolated by using the RNeasy lipid tissue mini kit (Qiagen, Hilden, Germany). Reverse transcription-polymerase chain reaction (RT-PCR) was performed as described in a previous study (Lee et al, 2018). The following primer pairs (Bioneer, Daejeon, Korea) were used: TNF-a forward 5 0 -GCG GAG TCC GGG CAG GTC TA-3 0 and TNF-a reverse 5 0 -TCC ACG ATT TCC CAG AGA AC-3 0 ; IL-6 forward 5 0 -CAC GGC CTT CCT ACT TCA C-3 0 and IL-6 reverse 5 0 -GGT CTT GGT CCT TAG CCA CT-3 0 ; IL-1b forward 5 0 -CCT CAG TGC GGG CTA TGA CC-3 0 and IL-1b reverse 5 0 -TCG GCC AAG ACA GGT CGC TC-3 0 ; C-reactive protein (CRP) forward 5 0 -GAA CTG GCG GGC ACT GAA CTA-3 0 and CRP reverse 5 0 -GGA GGT GCT TCA GGG TTC ACA-3 0 ; and b-actin forward 5 0 -TAA CCA ACT GGG ACG ATA TG-3 0 and b-actin reverse 5 0 -ATA CAG GGA CAG CAC AGC CT-3 0 .…”
Section: Reverse Transcription-polymerase Chain Reactionmentioning
confidence: 99%
“…Total proteins were extracted from homogenised gastrocnemius muscle and epididymal fat tissue using NP-40 lysis buffer (Elpis Biotech, Daejeon, Korea). Western blot assay was conducted according to previously described method (Lee et al, 2018). The membrane was incubated with primary antibodies against GLUT4, p-IRS-1, IRS-1 p-PI3K, PI3K, p-Akt, Akt, p-AMPK, AMPK, p-p38, p38, p-ACC, ACC, and a-tubulin (Cell Signaling Technology, Beverly, MA, USA) for 18-24 h at 4°C, and then by exposed to secondary horseradish peroxidase (HRP)-conjugated antibody (Bethyl Laboratories, Inc., Montgomery, TX, USA) for 2 h at 4°C.…”
Section: Western Blot Assaymentioning
confidence: 99%
See 1 more Smart Citation